Ustawa o nieodpłatnej pomocy prawnej, nieodpłatnym poradnictwie obywatelskim oraz edukacji prawnej z dnia 5 sierpnia 2015 r. – wybrane problemy - Daniluk, Dawid (PRAWO i WIĘŹ, 2026)
The system of free legal aid was established in 2015. It was intended to provide access to pre-trial legal assistance for individuals whose financial or life situation made them unable to bear the costs of legal services offered on the open market by attorneys at law and advocates. The assistance was originally meant to be provided, in principle, by professionals. The legislator deviated from these assumptions by creating a new service involving the provision of free civic counselling. The author attempts to assess the normative model of access to free aid and presents the most significant legislative changes that have been implemented over the years of the law’s existence.